POTENSI KONFLIK PASCA BENCANA: Komunitas Islam dan Khatolik di Desa Ngargomulyo - Nur Wahid Sofyan (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2018)
The potential conflict for post-disaster, especially between religious communities, is a fact that cannot be denied. This study portrays the potential between the Islamic and Catholic communities in Ngargomulyo Village after the Mount Merapi disaster. This research uses the framework of motive, incentive and apportunities theories popularized by Neil and Reigharts and the conflict and peace approach that was popularized by Johan Galtung. The results of the study showed that the potential confilict for post-disaster was caused by the unstable mental condition of the community and the unstable economic factors. Thus, it is expected that the role of humanitarian institutions is to provide capacity building programs for the community both through training, strengthening existing institutions in the community (RT, RW, PKK, Karang Taruna, churches, mosques, Islamic Boarding Schools, Community Group Schools /community). Other effects of disasters in the form of indirect conflict can also be mitigated by disaster management that includes aspects of mitigation response, good recovery and rehabilitation and overall distribution of aid, based on the principle of no harm in distributing aid and the principle of impartiality looking at ethnicity, religion, race and color, so that the issue of criticism does not interfere with the response period. In addition, humanitarian agencies and disaster management must consider aspects of local wisdom such as culture, the role of figure and involvement of local resources.